Quadrados latinos e quadrados mágicos - uma proposta didática - Farias, Fausto Gustavo (2017)
In this work we study the Latin Squares and the Magic Squares. We explore the mathematical teory and, above all, we study the link between theses objects. We bring the necessary information to support the teacher in the usage of Latin Squares and Magic Squares as content. Our goal is to discuss the usage of games and challenges like didatic tools, and to find a proposal to applicate him in the classroom.